2020
DOI: 10.1097/md.0000000000019766
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in the patients with chronic liver disease

Abstract: Background: Chronic liver disease is traditionally conceived as a risk factor for cardiovascular surgery. Transcatheter aortic valve implantation (TAVI) has recently burgeoned to precede surgical aortic valve replacement (SAVR) in patients with severe aortic stenosis at intermediate to high surgical risk. The evidence regarding TAVI in the patients with chronic liver disease is currently scarce.Methods: This article aims to assess the application of TAVI technique in the patients with chronic liver disease.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(88 reference statements)
0
3
0
1
Order By: Relevance
“…Similarly, due to associated coagulopathy, liver disease patients have an increased tendency to bleed [27]. In a previous meta-analysis, patients with chronic liver disease had a higher incidence of bleeding complications, need for blood transfusions, and mortality, which was further exacerbated by antiplatelet drug use [28,29]. As reported by Tchetche et al, 38.9% of patients undergoing TAVR received at least one transfusion [10,13,19,29].…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, due to associated coagulopathy, liver disease patients have an increased tendency to bleed [27]. In a previous meta-analysis, patients with chronic liver disease had a higher incidence of bleeding complications, need for blood transfusions, and mortality, which was further exacerbated by antiplatelet drug use [28,29]. As reported by Tchetche et al, 38.9% of patients undergoing TAVR received at least one transfusion [10,13,19,29].…”
Section: Discussionmentioning
confidence: 92%
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
“… References 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 …”
Section: Supporting Informationunclassified
“…Careful attention to dimensionless index, cross-sectional appearance of the valve, and further evaluation with left/right heart catheterization or TEE should be considered in patients with moderate or greater aortic stenosis. We consider TAVR in all patients prior to listing with severe aortic stenosis or moderate aortic stenosis with symptoms, as there are emerging data that TAVR can be performed safely in this population [24 ▪ ]. Echocardiography should be obtained when patients are euvolemic, as volume overload will worsen the degree of mitral and tricuspid regurgitation.…”
Section: Valvular Diseasementioning
confidence: 99%